Water Balance Study - Upper Gangetic Plain (Zone - V) October 1989 - Planning Commission (Planning Commission Government of India, 1989)
The Water Balance Study for the Upper Gangetic Plain (Zone V), conducted by the Operations Research Group in 1989, evaluates the availability, utilization, and sustainability of water resources in the region. Covering 143.66 lakh hectares with a predominantly agricultural population, the study assesses both surface and groundwater resources, analyzes current usage patterns, and projects future water demands, particularly under intensified cropping. Findings indicate a total water supply of 47,640 MCM and a projected agricultural demand of 69,757 MCM by 1994-95, with groundwater extraction accounting for 35% of recharge and localized salinity issues. The study emphasizes conjunctive use of water, improved canal efficiency, continuous monitoring, and targeted research to ensure sustainable management. The findings provide critical guidance for optimizing water utilization, enhancing agricultural productivity, and safeguarding water resources for future generations.
Planning Commission Agro-Climatic Regional Planning Unit
Keywords: Water Balance; Upper Gangetic Plain; Surface Water; Groundwater; Irrigation; Agricultural Demand; Canal Efficiency; Water Management; Climatic Conditions; Hydrology; Sustainable Practices; Water Resource Assessment